Effect of pseudohalogen groups on the optical properties and the structures of diorganotin coordination compounds based on the flexible ligand 1, 2, 3, 4‐tetra‐(4‐pyridyl)‐butane. (24th May 2017) - Amini, Mostafa M.; Najafi, Ezzatollah; Saeidian, Hamid; Mohammadi, Elham; Shahabi, Shiva Mosavi; Ng, Seik Weng
Abstract : To investigate the effect of pseudo‐halogen groups on the structure and optical properties of diorganotin(IV) coordination compounds the reaction of dimethyltin diisothiocyanate and dimethyltin dichloride with 1, 2, 3, 4‐tetra‐ (4‐pyridyl)‐butane (TPB) were studied. The results of spectroscopic data and structural analyses of prepared compounds showed that the reaction of Me2 SnCl2 with TPB ligand leads to the formation of a 2D organotin(IV) coordination polymer, while the replacement of chloride ions with thiocyanate ions as pseudohalogen groups in the structure of Me2 SnCl2 results in the development of a salt with an anion complex and a dimeric stannoxane as a side product. The results showed that the use of pseudo‐halogen groups instead of halogen groups in the structure of diorganotin(IV) dihalogen compounds could be as a suitable factor in the control of the structure of diorganotin(IV) coordination compounds. The investigation of optical properties of prepared compounds demonstrated that the use of pseudo‐halogen groups in the structure of diorganotin(IV) coordination compounds have an influence on their photoluminescence behavior. Abstract : The effect of pseudo‐halogen groups on the structure and optical properties of diorganotin(IV) coordination were investigated. Structural analyses showed that the reaction of Me2 SnCl2 with 1, 2, 3, 4‐tetra‐ (4‐pyridyl)‐butane ligand leads to the formation of a 2D organotin(IV) coordination polymer, while the replacement of chloride ions with thiocyanate ions in the structure of Me2 SnCl2 results to salt formation. Optical properties studies showed that the use of pseudo‐halogen groups in the structure of diorganotin(IV) coordination compounds have an influence on their photoluminescence behavior.